1993
DOI: 10.1111/j.1399-6576.1993.tb03595.x
|View full text |Cite
|
Sign up to set email alerts
|

Influence of high thoracic epidural anesthesia on left ventricular contractility assessed using the end‐systolic pressure‐length relationship

Abstract: The effect of high thoracic epidural anesthesia (TEA on left ventricular contractility was studied in a prospective clinical trial. Forty-eight patients with ASA physical status 1 and 2 and without cardiovascular disease were included in the study. Thirty-six patients scheduled for elective upper abdominal surgery were randomly assigned to Group 1 (TEA, bupivacaine 0.25%, n = 12), Group 2 (TEA, bupivacaine 0.5%, n = 12) or to Group 3 (control without TEA, n = 12). TEA induced a sensory block which extended ove… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
18
0
1

Year Published

1995
1995
2018
2018

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(21 citation statements)
references
References 39 publications
2
18
0
1
Order By: Relevance
“…Goertz et al reported that high thoracic EA decreases Ees in humans by 50%. 30 The decrease in Ees in humans is similar to that observed during thoracolumbar EA in the present study. Thoracolumbar EA causes the blockade of afferences and efferences between the heart and the central nervous system (cardiac denervation).…”
Section: Discussionsupporting
confidence: 76%
See 1 more Smart Citation
“…Goertz et al reported that high thoracic EA decreases Ees in humans by 50%. 30 The decrease in Ees in humans is similar to that observed during thoracolumbar EA in the present study. Thoracolumbar EA causes the blockade of afferences and efferences between the heart and the central nervous system (cardiac denervation).…”
Section: Discussionsupporting
confidence: 76%
“…In spite of several previous clinical and experimental studies, questions remain about the effect of EA on left ventricular contractility, which has variously been reported to be unchanged, 27,28 decreased, 29,30 or even increased. 31,32 This variability is attributable to differences in study design, the subjects studied, and the measures used to assess left ventricular contractility.…”
Section: Discussionmentioning
confidence: 99%
“…Goertz et al [9] administered about 20ml of mepivacaine (0.25% and 0.5%) in the thoracic epidural space and found that TEA produced no significant change in any of the systolic, diastolic, MAP, HR, LV endsystolic and end-diastolic areas, and ESWS, although the LV maximal elastance (Emax) was reduced significantly by TEA. E .... is known to be a most powerful indicator of LV contractility independently of loading conditions, derived from the pressure-volume relationship [15].…”
Section: Discussionmentioning
confidence: 96%
“…High TEA has been reported to impair LV systolic function with a blockade of cardiac sympathetic segments [8][9][10][11][12]. However, this observation remains controversial.…”
Section: Discussionmentioning
confidence: 98%
“…The extent of sympatholysis may be variable, and only loosely related to the sensory level. TEA sympathetic blockade extending to the "cardiac accelerators" (T1-T4) likely exerts a negative inotropic eff ect, ( 8 ) in addition to eff ects on loading conditions. Vascular tone: TEA sympatholysis results in vasodilation and increased venous and arterial capacitance.…”
Section: Cardiovascular Eff Ects Of Teamentioning
confidence: 99%